2016
DOI: 10.1016/j.jcrs.2016.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular lens power formula accuracy: Comparison of 7 formulas

Abstract: None of the authors has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
199
4
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(237 citation statements)
references
References 22 publications
25
199
4
9
Order By: Relevance
“…In total, there are 1161 eyes are enrolled from the 10 included studies (characteristics shown in Table ) . The sample size ranged from 15–608 eyes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, there are 1161 eyes are enrolled from the 10 included studies (characteristics shown in Table ) . The sample size ranged from 15–608 eyes.…”
Section: Resultsmentioning
confidence: 99%
“…In total, there are 1161 eyes are enrolled from the 10 included studies (characteristics shown in Table 1). [12][13][14][15]18,19,[24][25][26][27] The sample size ranged from 15-608 eyes. All of the trials utilized IOL master for AL measurement.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, Kane et al[21] reported that the mean prediction error of the IOLMaster in eyes with an axial length of ≥26 mm (version 5.4) was 0.21 dpt using the Haigis formula, –0.20 dpt using the Barrett Universal II, and 0.392 dpt or 0.370 dpt as the MedAE. To reduce postoperative refractive error, Wang and colleagues[22, 23] proposed axial length correction formulas for the Holladay I, Haigis, SRK/T, and Hoffer Q formulas in eyes with an axial length of ≥25 mm.…”
Section: Discussionmentioning
confidence: 99%
“…As defined previously [3], refractive prediction error (PE) was calculated as the difference between postoperative objective refraction expressed as spherical equivalent (ORSE) and the predicted spherical equivalent of the refraction obtained from the preoperative biometry (IOL Master 500, Carl Zeiss Meditec AG, Jena, Germany). Absolute error (AE) was calculated in the standard way as the absolute value of the refractive PE.…”
Section: Methodsmentioning
confidence: 99%